Unraveling the influences of hemodynamic lag and intrinsic cerebrovascular reactivity on functional metrics in ischemic stroke - Luoyu Wang; Xiumei Wu; Jinyi Song; Yanhui Fu; Zhenqiang Ma; Xiaoyan Wu; Yiying Wang; Yulin Song; Fenyang Chen; Zhongxiang Ding; Yating Lv (NeuroImage)
Resting-state functional magnetic resonance imaging (rs-fMRI) is a prominent tool for investigating functional deficits in stroke patients. However, the extent to which the hemodynamic lags (LAG) and the intrinsic cerebrovascular reactivity (iCVR) may affect the rs-fMRI metrics in different scales needs to be clarified for ischemic stroke. In this study, 73 ischemic stroke patients and 74 healthy controls (HC) were recruited to investigate how the correction of the LAG and/or iCVR would influence resting-state functional magnetic resonance imaging (rs-fMRI) metrics of three different spatial scales (local-scale, meso-scale and global-scale) in ischemic stroke. The analysis revealed that the Stroke pattern of all functional metrics using different correction strategies resembled the HC pattern. The highest overlap was observed in the Stroke pattern with correction for both LAG and iCVR, while the pattern without correction showed the lowest overlap. Most functional metrics after correction showed higher sensitivity in detecting between-group differences than those without correction. Moreover, our results were generally reproducible in an independent dataset. Collectively, these findings emphasize the necessity of considering LAG and iCVR effects to investigate stroke-related functional alterations, and highlight the significance of correction strategies for accurately interpreting the findings in rs-fMRI study of ischemic stroke.